Respuesta :
Ok work is shown below:
F = mg + ma
-ma + F = mg
-ma = mg - F
-a = g - F/m
a = F/m - g
Hope this helps you out!
ANSWER
The correct answer is option D.
[tex]a = \frac{F}{m}-g[/tex]
EXPLANATION
The given formula is
[tex]F = mg + ma[/tex]
We want to solve this formula for a, so we add
[tex] - mg[/tex]
to both sides of the equation to get,
[tex]F - mg=ma[/tex]
We now divide through by m, to obtain,
[tex] \frac{F}{m} - \frac{mg}{m} = \frac{ma}{m} [/tex]
Let us cancel out the common factors to get,
[tex] \frac{F}{m} - g =a[/tex]
We can also rewrite this to obtain,
[tex]a = \frac{F}{m}-g[/tex]
Therefore the correct answer is D.
The correct answer is option D.
[tex]a = \frac{F}{m}-g[/tex]
EXPLANATION
The given formula is
[tex]F = mg + ma[/tex]
We want to solve this formula for a, so we add
[tex] - mg[/tex]
to both sides of the equation to get,
[tex]F - mg=ma[/tex]
We now divide through by m, to obtain,
[tex] \frac{F}{m} - \frac{mg}{m} = \frac{ma}{m} [/tex]
Let us cancel out the common factors to get,
[tex] \frac{F}{m} - g =a[/tex]
We can also rewrite this to obtain,
[tex]a = \frac{F}{m}-g[/tex]
Therefore the correct answer is D.